Revenues and Welfare in Auctions with Information Release - Nora Szech; Nikolaus Schweizer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Auctions are the allocation-mechanisms of choice whenever goods and information in a market are scarce. Therefore, understanding how information in these markets affects welfare and revenues is of fundamental interest. We introduce new mathematical concepts, k- and k-m-dispersion, for understanding the impact of information. With these tools, we study the comparative statics of welfare versus revenues for markets with one or more objects and varying numbers of bidders. Depending on which parts of a distribution of valuations are most affected by release of information, welfare may react more strongly than revenues, or vice versa.
Keywords: D44; D82; D47; 330